The Perception of the Anesthesiologist Among the Medical, Paramedical and Administrative Staff - Selim, Jean; Selim, Marc; Demailly, Zoé; Wable, Thierry; Clavier, Thomas; Besnier, Emmanuel; Dureuil, Bertrand; Veber, Benoît; Djerada, Zoubir; Compere, Vincent (Frontiers in Medicine, 2022)
Introduction: Anesthesia remains a young medical discipline still relatively unknown by the general public and probably by some health professionals. The objective of the study was to evaluate the perception of anesthesiologist by health professionals working with this specialty Methods: We distributed a computerized survey to physicians, residents, paramedical, midwives and, administrative staff in different hospitals between April and July 2018 in Normandy, France. The survey included 38 questions on 6 different topics: communicated image, skills and knowledge, communication, place in patient care, workload and initial anesthesiologist formation. The survey was validated by a semi-directive interview methodology. A Likert scale from -2 to +2 ("completely disagree" to “completely agree”) was used for each item. Results: 629 out of 2000 surveys sent were analyzed. The anesthesiologist conveys an image of serenity (+0.94 ±0.79), has a high degree of responsibility (+1.72 ±0.59) with important decision-making power (+1.39 ±0.82). He guarantees patient safety and comfort (+1.07 ±0.88) with his/her dual competence in anesthesia and intensive care (+1.36 ±0.82). Anesthesiology requires teamwork (+1.68 ±0.58) and good communication skills (+1.48 ±0.73). The anesthesiologist is not perceived as a service provider (-0.33 ±1.15) but is the physician responsible for perioperative care (+1.69 ±1.00). His/her workload is moderately perceived as high (+0.71 ±1.17) but is confronted with potentially conflictual relationships with colleagues from other specialties (+1.40 ±0.68) and stressful situations (+1.44 ±0.80). Conclusion: The overall perception of the anesthesiologist in our study appears to be good.